2016
DOI: 10.1177/1479164115624681
|View full text |Cite
|
Sign up to set email alerts
|

Review of gestational diabetes mellitus effects on vascular structure and function

Abstract: Vascular dysfunction has been described in women with a history of gestational diabetes mellitus. Furthermore, previous gestational diabetes mellitus increases the risk of developing Type 2 diabetes mellitus, a risk factor for cardiovascular disease. Factors contributing to vascular changes remain uncertain. The aim of this review was to summarize vascular structure and function changes found to occur in women with previous gestational diabetes mellitus and to identify factors that contribute to vascular dysfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 24 publications
1
16
0
1
Order By: Relevance
“…Consistent with our results, total cholesterol level and triglycerides in women with history of GDM were elevated in postpartum compared with controls (7,26,27). Increased low-density lipoprotein (LDL) was reported in Caucasian women 6 years after GDM pregnancy (28, 29), Retnakaran et al reported significant differences in total cholesterol, LDL, triglycerides, total cholesterol to HDL ratio with glucose status in pregnancy at 3 months postpartum in Canadian women (30).…”
Section: Comparison Of Postpartum Lipids Levels In Women With Gdm Andsupporting
confidence: 79%
See 1 more Smart Citation
“…Consistent with our results, total cholesterol level and triglycerides in women with history of GDM were elevated in postpartum compared with controls (7,26,27). Increased low-density lipoprotein (LDL) was reported in Caucasian women 6 years after GDM pregnancy (28, 29), Retnakaran et al reported significant differences in total cholesterol, LDL, triglycerides, total cholesterol to HDL ratio with glucose status in pregnancy at 3 months postpartum in Canadian women (30).…”
Section: Comparison Of Postpartum Lipids Levels In Women With Gdm Andsupporting
confidence: 79%
“…Some previous studies reported similar or lower LDL-C in none-obese women with GDM, while obese women with GDM had higher level of this component compared with controls. Obese GDM-exposed women had lower HDL-C, while there were no significant differences between HDL-C level in non-obese women with GDM and controls (7). Elevated triglyceride in combination raised LDL-cholesterol, and low HDL-C are types of dyslipidemia associated with obesity.…”
Section: Impact Of Pre-pregnancy Overweight and Obesitymentioning
confidence: 93%
“…GD, a glucose intolerance first recognized during pregnancy, is an independent risk factor of disease in both offspring and mother [60,61]. The hyperglycemia occurring during pregnancy induces long-term phenotypic alterations in fetal endothelial cells, changes in miR-101 expression levels, as well as in those of Enhancer of Zester Homolog 2 (EZH2), its target [24].…”
Section: Mirna-associated Pregnancy Complicationsmentioning
confidence: 99%
“…The decrease in the level of 1,25(OH) 2 D 3 , reduction in expression of soluble Klotho, activation of the reninangiotensin system, increase in sodium retention in the kidneys, increase in inflammatory markers, and hypophosphatemia could be explanations for the effect of FGF23 on the cardiovascular system. GDM contributes to vascular dysfunction, as recently reported in a metaanalysis (34). The hypothesis of whether FGF23 levels are high in patients with GDM, which brings increased risk of cardiovascular disease, was tested in our study.…”
Section: Resultsmentioning
confidence: 89%